Review of the leafhopper genus Makilingia Baker (Hemiptera: Cicadellidae: Mileewinae) - Dietrich, Christopher H.; Zahniser, James N. (Zootaxa, 2019)
The taxonomy of the leafhopper genus Makilingia Baker is reviewed based on comparative morphological study of types and other specimens. Twenty-six species are recognized as valid including ten new species described and illustrated herein: M. davaoensis n. sp. M. lobata n. sp., M. maculamima n. sp., M. nigramima n. sp., M. paranigra n. sp., M. siamensis n. sp., M. tenebrifrons n. sp., M. uncinata n. sp., M. viraktamathi n. sp., and M. xanthopicta n. sp. Makilingia siamensis n. sp. represents the first known occurrence of the genus outside the Philippine Archipelago and the first record for Thailand. Makilingia simillima Baker, n. stat., formerly treated as a variety of M. variabilis Baker, is elevated to full species status based on distinctive differences in the male genitalia. Lectotypes are designated for several species described by Baker. The male genitalia of these species are described and illustrated for the first time and a key to all known species is provided.